2022
DOI: 10.48550/arxiv.2206.02346
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Convergence and sample complexity of natural policy gradient primal-dual methods for constrained MDPs

Abstract: We study sequential decision making problems aimed at maximizing the expected total reward while satisfying a constraint on the expected total utility. We employ the natural policy gradient method to solve the discounted infinite-horizon optimal control problem for Constrained Markov Decision Processes (constrained MDPs). Specifically, we propose a new Natural Policy Gradient Primal-Dual (NPG-PD) method that updates the primal variable via natural policy gradient ascent and the dual variable via projected sub-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The primal-dual methods, also called Lagrangian methods, are designed to address Lagrange dual problems. Ding et al (2022) introduced a natural policy gradient-based primal-dual method and demonstrated its convergence to an optimal policy at a specified convergence rate. Another primal-dual method, proposed by Bai et al (2022), ensures that a trained policy results in zero constraint violations during evaluation.…”
Section: Related Workmentioning
confidence: 99%
“…The primal-dual methods, also called Lagrangian methods, are designed to address Lagrange dual problems. Ding et al (2022) introduced a natural policy gradient-based primal-dual method and demonstrated its convergence to an optimal policy at a specified convergence rate. Another primal-dual method, proposed by Bai et al (2022), ensures that a trained policy results in zero constraint violations during evaluation.…”
Section: Related Workmentioning
confidence: 99%